1991
DOI: 10.1007/bf02576657
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 2-fluoro-2-deoxy-d-glucose uptake and ATP level for evaluating drug effects in neoplastic cells

Abstract: The glucose analogue 2-fluoro-2-deoxy-D-glucose (FDG) was used to study chemosensitivity of two human ovarian cancer cell lines and of murine L1210 cells. Cell viability was determined by measuring intracellular adenosine triphosphate (ATP) with a bioluminescence method, which has been shown to correlate closely with trypan blue, stem cell, and [3H]TdR assays. All three cell lines were sensitive to cytostatic drugs, which exerted a parallel decrease in the intracellular FDG and ATP levels. The two measures cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Measurement of FDG uptake in tumors may not only assist in oncologic imaging, but can also be useful in the evaluation of the treatment effect of anti-glycolytic agents [23]. Several studies showed that FDG may be used to study drug effects in vitro [24,25]. Our study further validated this principle in vivo, by showing lesser FDG uptake after 3-BrPA treatment, which was specific for tumor tissue.…”
Section: Discussionsupporting
confidence: 79%
“…Measurement of FDG uptake in tumors may not only assist in oncologic imaging, but can also be useful in the evaluation of the treatment effect of anti-glycolytic agents [23]. Several studies showed that FDG may be used to study drug effects in vitro [24,25]. Our study further validated this principle in vivo, by showing lesser FDG uptake after 3-BrPA treatment, which was specific for tumor tissue.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, it has been shown that the killing of neoplastic cells by cytostatic drugs is associated with decreased ATP content and FDG uptake. This indicates that FDG uptake is closely linked with ATP production and that not only ATP but also FDG could be used to study drug effects in vitro [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the ability of functional imaging techniques to detect subclinical alterations in tumour physiology and biochemistry resulting from efficacious therapy [1,6,13,15,18,20]. These alterations may occur long before a morphologic change in the tumour mass is apparent.…”
Section: Introductionmentioning
confidence: 99%